Synthesis and characterization of thermal conductivity of nanofluids based on Ag decorated-CNTs/graphene hybrid materials - Ngoc Anh Nguyen; Van Trinh Pham; Hung Thang Bui; Van Chuc Nguyen; Tuan Hong Nguyen; Ngoc Minh Phan; Ngoc Hong Phan (Vietnam Journal of Science, Technology and Engineering, 2017)
In this work, we present a new nanofluid based on silver nanoparticles decorated on the functionalized carbon nanotubes-graphene sheet (hybrid) materials. Briefly, carbon nanotubes and graphene sheets were first functionalized with a hydroxyl group and carboxyl group respectively. The hybrid material was decorated with silver nanoparticles via chemical reduction method with the assistance of sodium hydroxyl. Finally, the obtained Aghybrid material was dispersed in ethylene glycol solution (EG) to form the nanofluid without any surfactant. The thermal conductivity of nanofluid was measured for different weight concentrations at different temperatures. The results showed an increase in thermal conductivity of up to 86% for 0.045% weight concentration at 55oC. This enhancement was due to the high thermal conductivity of graphene, carbon nanotubes (CNTs), and Ag nanoparticles as well as the higher surface area of Ag nanoparticles decorated on graphene and CNTs structures. The results of Transmission Electron Microscope (TEM), X-rays diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) indicated that the silver nanoparticles were formed on the surface of carbon nanotubes and graphene sheets.